Six Sigma case studies with Minitab - Pochampally, Kishore K.; Gupta, Surendra M. (CRC Press, 2014)
Six Sigma is one of the most widely used quality improvement methodologies today, both in manufacturing and service industries. Minitab® is a statistical software package that is often used in conjunction with Six Sigma projects. This book illustrates the application of Minitab® for Six Sigma projects, using case studies in a variety of sectors, such as healthcare, manufacturing, airline, and fast food. Detailed steps and screenshots are provided to explain how to use a number of quality analysis and improvement tools in Minitab®. Figures will include Minitab® screenshots and Minitab® worksheets for the case studies will be available for download.